Ash deposition and heat transfer characteristics on the convective heating surface of calcium‐rich Zhundong coal combustion in a 0.4‐MWth facility. Issue 3 (18th May 2022) - He, Xiang; Jin, Jing; Yang, Haoran; Lv, Weizhi; Ma, Dafu; Shi, Hongfei; Chen, Duanyu
Abstract: Thermal power plants in Zhundong area of Xinjiang equip Π‐typed boiler widely in recent years. With the increasing ratio of Zhundong coal in blended fuels, the slagging is strengthened. And the boiler shutdown was caused by ash deposition on the convective heating surface frequently. In order to study the mechanism of this problem, a 0.4‐MWth pilot‐scale facility was built and expected to study ash deposition and heat transfer characteristics on the convective heating surface of 100% burning calcium‐rich Zhundong coal. Thermodynamic model calculation was implemented on the heat transfer characteristics of two groups of tube panels, on which ash samples were collected after experiments. Then, simulation calculation was applied by software for verification. The ash samples were characterized by X‐ray diffraction spectroscopy (XRD) and scanning electron microscopy (SEM) coupled with energy dispersive X‐ray detector (EDX). FactSage 7.3 thermochemical software package and a high‐temperature viscometer were also used to figure out the viscosity‐temperature characteristics. Results showed that a "step change" of heat transfer characteristics occurred when the flue gas temperature of inlet tube panel #2 approached to 1000°C. After the "step change, " the heat transfer characteristics became stable. The ash deposition mainly consisted of silicon‐calcium compounds of tube panel #1, while in contrast, that of tube panel #2 consisted of gehlenite, CaSO4, and Na2 SO4 . The ratio of liquid phase in raw coal ash samples increased sharply when the flue gas temperature exceeded 1030°C. With the increase of surface temperature of fouling tube panel, the CaSO4 would be decomposed to release CaO, which reacted with gehlenite or other compounds to form low temperature eutectics. The fouling of ash would transfer to slagging and lead to the deterioration of ash deposition, which induced the formation of "step change" during the experiment.